Dental Restorative Digital Workflow: Digital Smile Design from Aesthetic to Function - Gabriele Cervino; Luca Fiorillo; Alina Vladimirovna Arzukanyan; Gianrico Spagnuolo; Marco Cicciù (MDPI AG, 2019)
Breakthroughs in technology have not been possible without influencing the medical sciences. Dentistry and dental materials have been fully involved in the technological and information technology evolution, so much so that they have revolutionized dental techniques. In this study, we want to create the first collection of articles on the use of digital techniques and software, such as Digital Smile Design. The aim is to collect all of the results regarding the use of this software, and to highlight the fields of use. Twenty-four articles have been included in the review, and the latter describes the use of Digital Smile Design and, in particular, the field of use. The study intends to be present which dental fields use “digitization„. Progress in this field is constant, and will be of increasing interest to dentistry by proposing a speed of treatment planning and a reliability of results. The digital workflow allows for rehabilitations that are reliable both from an aesthetic and functional point of view, as demonstrated in the review. From this study, the current field of use of Digital Smile Design techniques in the various branches of medicine and dentistry have emerged, as well as information about its reliability.